Sex education and gender differences in reproductive health and population management in Jordan, Guimaras - Cuadra, Venus O.
The study aims to achieve the following objectives: To know the current level of awareness of the community regarding Sex Education concerns, to identify the different Reproductive Health problems of both women and men, to determine the existing contraceptive methods and practices used by women and men in controlling population increase and identify those methods that are acceptable and not acceptable in both gender in the community. The study was conducted among household member, ages 15-45 years. there were 87 total respondents and a systematic random sampling was employ to select the subjects. A survey method was used to gather data useful in the study. Since the study is descriptive, frequency and percentage distribution mehtods were used to analyze the data. Result in general showed that sex education intervention of government and non government organization can help increase the level of awareness of both men and women in the community. Only few of the respondents experienced reproductive health problems and most of these can be considered less serous. Knowledge or awareness is one factor that can affect the use and acceptability of the contraceptive methods and practices, however, there are other factors that must be consider.